A valoração dos impactos ambientais associados à expansão da Matriz Elétrica Brasileira: proposta de instrumentos econômicos para a promoção das fontes alternativas e limpas - Laura Araujo Alves (2009)
Despite of the great potential of exploration in Brazil, alternative and clean energy sources still have an inexpressive use. The market failure is one of the main causes which compromise the expansion of this type of energy. Therefore, in order to achieve a significant grow of these sources, it is essential that governments elaborate environmental politics in which the economic instruments considered adequately promote their participation in the electrical energy generation sector. In this context, this work discusses the environmental impacts related to the different technologies used in power generation, aiming at proposing solutions for the sustainability of the Brazilian Electrical Sector. At first, methodologies for evaluating the environmental impact costs related to human health and climatic changes are applied with the objective of finding the economic values, measured in Reais/kWh. Based on these values, the expansion scenario predicted by the Plano Decenal de Expansão de Energia 2007/2016 is evaluated. This evaluation aims at describing the nations situation regarding the environmental costs paid by the society in case of the effective implementation of this government plan. The costs related to human health, considering that they represent directly the value of statistical life concept, showed extremely high values. The costs related to climate changes are strongly related to fossil fuels thermoelectric plants and, therefore, small increments in the production of energy that use these sources represent great increase in environmental costs. Finally, proposals of economic instruments in the context of environmental politics are discussed. They are based on national tendencies and international experiences and could be adopted in Brazil to promote clean and alternative sources of energy. It is shown that different opportunities exist and should be evaluated in detail when elaborating a consolidated environmental politic for Brazil.